(untitled) (Journal of Informatics Education and Research, 2025)
The integration of sustainability considerations into capital budgeting decisions is increasingly recognized as crucial for organizations striving to align financial investments with long-term environmental, social, and economic goals. This comprehensive literature review examines the intersection of sustainability and capital budgeting, encompassing key concepts, methodologies, challenges, and opportunities. Drawing upon a wide range of scholarly articles, case studies, and industry reports, this review provides insights into current practices, emerging trends, and future directions in sustainable capital budgeting. The review has been divided into multiple sections. In one section, all the reviews which identify current lacunae in sustainability incorporation in capital budgeting has been provided. In another section, logical reasons to incorporate sustainability have been discussed and emphasized upon. The third section discusses aspects of sustainability which have already been considered in the capital budgeting process. The fourth section discusses aspects of sustainability incorporated indirectly into cost of capital which is related to capital budgeting. Finally, the paper discusses research gaps and scope of future research.